Horror Film Creation and Control Budget Production: Case Study Black Full Moon - ธาดาอำนวยชัย มนฑิรา (Siam Communication Review, 2017)
Horror Film Creation and Control Budget Production: Case Study Black Full Moon consists of two objectives. First is to study of horror film creation which is based on true story and its storytelling which is accepted by horror story audiences. Second is to study horror film creation which is controlling production budget in order to survive in film industry at the present. Framework theories of this study consist of film production process, creative research concept and horror story-telling concept. Research methodology of Horror Film Creation and Control Budget Production: Case Study Black Full moon is qualitative research which is participatory observation which the researcher is executive producer of this film. Another research methods are in-depth interview. The interviewees are director of this film and story-teller whom tell haunted scout camp. More addition gather all film documents as film script, call-sheet, film poster which is uploading in facebook of Logo Motion Pictures and facebook audiences opinion on poster which post in facebook: Logo Motion Pictures. The studied shows that film production process of Bastian (2006) and creative research concept both concepts seem similar. Development in film production process is pair with design concept in creative research concept. The second is Preproduction which is pair with design visualization and design development in creative research concept. The third is Production which is pair with design construction. And the fourth of film production process is Postproduction which are pair with design presentation and design evaluation.